(untitled) (Research, Society and Development, 2020)
Based on requirement that must to fulfill that the object is able to be a object guarantee so Trademark Rights is qualify the requirement as object guarantee because have economic value and able to transferred with written agreement. In Juridical, existence of trademark rights is guarantee legal certainty for repayment of debtor debt or implementation of an achievement although in practice banking trademark rights only as additional guarantee. Guarantee institution that possible to burden it is mortgage or fiduciary guarantee. In this article this is focusing on fiduciary guarantee. When the debtor wanprestasie so the trademark rights as fiduciary object guarantee allow doing execution either by parate execution, executorial title or by selling privately made agreement. However, creditor or debtor is able to make an effort by finding buyers who are willing to buy the trademark rights. Whenever a buyer is found and serve so a deed of transfer is made on trademark in authentic then it follows with removal of fiduciary guarantee and recording of transfer of trademark rights that registered to Director General IPR until transfer of trademark rights besides giving legal certainty for buyer and also binding the third party.